PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KUALITAS SUMBER DAYA MANUSIA, DAN PENERAPAN SISTEM AKUNTANSI TERHADAP KINERJA SATUAN KERJA PERANGKAT DAERAH (SKPD). (Studi Empiris pada Kabupaten Rokan Hulu) - Widayati, Sandy; Taufik, Taufeni; Idrus, Rahmiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study aimed at finding out the effect of: (1) budgeting participation on the performances SKPD, (2) human resources quality on the performances SKPD, (3) the implementation of accounting information system on the performances SKPD, and (4) budgeting participation, human resources quality, and the implementation of accounting information system on performances SKPD. The study was conducted at the Local Government working unti devices in Rokan Hulu, made based on a quantitative, since the data obtained were in a form of figures. The samples were selected based on a purposive sampling technique by involving 80 respondents. These results indicate that the participation budgeting significant effect on the performance of SKPD because thitung 2.316> 1.000 ttabel with significant value of 0.023, significantly influence the quality of human resources SKPD performance because thitung 2.053> 1,000 ttabel with significant value 0.013, and Application of Accounting System significantly affect the performance of SKPD because thitung 5.263> 1.000 ttabel with significant value 0.00.The results provide evidence that the Budgetary Effects of Participation, Quality of Human Resources and Accounting System Implementation significant effect on SKPD Performance Against Rokan Hulu through multiple correlation coefficient (R) of 0.836 and a very strong relationshipKeywords: Participation,Budget,Quality,Accounting and Performance